The Test for Creative Thinking–Drawing Production Test in Preschool Children with Predominantly Migration Background—Psychometrics of the German TCT-DP. Issue 2 (3rd April 2018) - von Steinbüchel, Nicole; Meeuwsen, Mirjam; Poinstingl, Herbert; Kiese-Himmel, Christiane
Abstract : The study examined the psychometric properties of the German version of the Creative Thinking – Drawing Production Test (TCT-DP). This test evaluates creative potential with 14 content-related criteria, constituting a total score. Age norms exist for children from 4–16 years. A total of 269 children with predominantly migrant background, aged 36–71 months, from German preschools participated. Total scores of 4- and 5-year-old children were significantly below the German age norms published in the test manual, but did not differ with the degree of the migrant background (both vs. one or none migrant parents). In contrast to boys, scores from girls were slightly higher. Discriminant validity could be confirmed: Total scores did correlate neither with intelligence, nor with gender, fine motor skill, educational, or socio-economic status of the parents. The German TCT-DP respectively revealed acceptable internal consistency (Cronbach's α = .69–.73). For the first time, cumulative percentages for 3-year-olds are provided as a kind of preliminary age norm. The German TCT-DP proved to be applicable in 3-year-old children with migrant background, albeit not all content-related criteria can be interpreted. Its psychometric properties support its use for research rather than for clinical purposes.